Odpowiedzi

Najlepsza Odpowiedź!
2010-04-13T17:23:57+02:00
A) k=7n / : 7
k:7=n

b) a=k+6
a-6=k

c) z=7-y
y=7-z

d) d=a+bc
d-a=bc / : b
(d-a) : b=c

e) x=2k+1
x-1=2k / : 2
(x-1): 2 =k

f) 2k=7n+5
2k - 5 = 7n / : 7
(2k - 5) :7 = n
190 4 190
2010-04-13T17:24:30+02:00
A)k=7n; n
n=k/7
b)a=k+6; k
k=a-6
c)z=7-y; y
y=z-7
d)d=a+bc; c
c=d-a(w liczniku)/b(w mianowniku)
e) x=2k+1; k
-2k=1-x/:-2
k=x-1(w liczniku)/2
f)2k=7n+5; n
-7n=5-2k
n=2k-5(w liczniku)/7
64 3 64
2010-04-13T17:27:35+02:00
A) k=7n /:7
n=k:7
b)a=k+6
k=a-6
c)z=7-y
-y=z-7 /*(-1)
y=-z+7
d)d=a+bc; c
d=a+bc
d-a=bc /:b
c=(d-a):b
e) x=2k+1; k
x-1=2k /:2
k=(x-1):2
f)2k=7n+5; n
7n=2k-5 /:7
n=(2k-5):7
123 4 123